Matrilineal Kinship at Sea in Bougainville, Papua New Guinea - Katharina Schneider (Humaniora, 2018)
This paper explores matrilineal kinship in the Buka area, in the Autonomous Region of Bougainville, from the perspective of saltwater people on Pororan Island. In Bougainville and elsewhere in Melanesia, anthropological research has highlighted the importance of joint work in the gardens, of sharing and exchanging garden food, and of negotiations of access to land for kinship and relatedness in the region. Where does this leave saltwater people, who often have only small areas of land of their own, take little interest in gardening and depend on traded sweet potatoes or imported rice for meeting their subsistence needs? In the first part of this paper, I indicate “landed” bias in anthropological research on kinship, including matrilineal kinship. I then suggest complementary descriptive and analytic terms that may be useful for researchers who want to understand kin relations among saltwater people, based on my experiences among Pororan Islanders in Bougainville. Finally, I indicate the theoretical contribution that these terms can make to research on kinship in landed settings, as well.